Repurchase Intention Model of Generation Z Smartphone Products: Analysis of Brand Identity and Brand Love as Predictors - Butarbutar, Novita; Halim, Fitria; Fenny, Fenny; Sudirman, Acai (Cita konsultindo, 2024)
This study aims to analyze the influence of brand identity and brand love on the repurchase intention of smartphone products among Generation Z. This study uses a quantitative method with samples taken using a purposive sampling technique with a targeted number of respondents of around 200 people. By collecting survey data from Generation Z, which uses various smartphone brands, this study uses statistical analysis with SPSS to test the relationship between brand identity, brand love, and repurchase intention. The study's results indicate that brand identity and brand love significantly positively influence consumer intention to repurchase the same smartphone product. The implications of this study provide important insights for marketers in building more effective marketing strategies for the Generation Z target market. Marketers need to strengthen brand identity through elements relevant to consumer values ​​and lifestyles and create deep emotional connections to build brand love. Thus, smartphone companies can increase consumer loyalty and repurchase intentions, which is essential in this highly competitive market.